2015
DOI: 10.3389/fnhum.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindles Predict Stress-Related Increases in Sleep Disturbances

Abstract: Background and Aim: Predisposing factors place certain individuals at higher risk for insomnia, especially in the presence of precipitating conditions such as stressful life events. Sleep spindles have been shown to play an important role in the preservation of sleep continuity. Lower spindle density might thus constitute an objective predisposing factor for sleep reactivity to stress. The aim of this study was therefore to evaluate the relationship between baseline sleep spindle density and the prospective ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 47 publications
(60 reference statements)
3
32
0
3
Order By: Relevance
“…Furthermore, related studies also demonstrated that sleep spindles measured on a normal, quiet/undisturbed night of sleep were predictive of sleep quality on a subsequent night in a noisy environment (Dang-Vu et al, 2010). Moreover, baseline sleep spindles during a normal, quiet/undisturbed night of sleep could predict scores on the insomnia severity index during a disturbed night of sleep (Dang-Vu et al, 2015). In other words, sleep spindles from a normal, undisturbed night of sleep have predictive value (and are thus valid measures) of the continuity of sleep.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, related studies also demonstrated that sleep spindles measured on a normal, quiet/undisturbed night of sleep were predictive of sleep quality on a subsequent night in a noisy environment (Dang-Vu et al, 2010). Moreover, baseline sleep spindles during a normal, quiet/undisturbed night of sleep could predict scores on the insomnia severity index during a disturbed night of sleep (Dang-Vu et al, 2015). In other words, sleep spindles from a normal, undisturbed night of sleep have predictive value (and are thus valid measures) of the continuity of sleep.…”
Section: Introductionmentioning
confidence: 98%
“…11 Additional phenotypes are emerging through the use of sleep biomarkers related to depressive and anxiety disorders and/or stress-related insomnia. 12,13 Critical cost-benefit analysis discussion remains paramount when the practitioner and patient decides if and what type of pharmacotherapeutic sleep agent is most appropriate for treating their respective sleep complaint. 14,15 Moreover, the United States Food and Drug Administration has continued to stress the importance of monitoring all classes of sleep aides due to concerns over safety and habituation 16,17 calling for the potential clinical value for repeated-measures dose-response EEG studies.…”
Section: Scientific Investigationsmentioning
confidence: 99%
“…After rejection of periods when the absolute amplitude is ≥ 500 µV, the signals were notch filtered, and then infinite impulse response band pass-filtered to obtain 16 Hz samples of the power values for delta (1-3.5 Hz), Delta C (delta power corrected for ocular activity), theta (4-6.5 Hz), alpha (8-12 Hz), sigma (12)(13)(14)(15)(16), beta (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and EMG bands ( > 40 Hz with a 80 Hz, 3 dB rolloff). A second set of power values was obtained after application of a 0.75-Hz highpass filter.…”
Section: Softwarementioning
confidence: 99%
“…Nors Lietuvoje atliktų tyrimų, susijusių su studentų patiriamu nerimu, rezultatai skiriasi nuo užsienio literatūroje pateikiamų rezultatų, negalima paneigti nerimo problemos, o kartu ir nerimo įtakos miego kokybei [26]. Įrodyta, jog nemiga yra dažnesnė asmenims, turintiems depresijos ir nerimo simptomų [27]. Estijoje, Tartu universitete, atlikto tyrimo, kuriame dalyvavo 413 medicinos studentų, duomenimis, 21,9 proc.…”
Section: įVadasunclassified